(untitled) (Scientific journal of the Fergana State University, 2024)
This article analyzes the influence of the indicator, indicator and value of world soil health on the indicators of the function of their role in the soil. Due to the sharp decline in soil quality, the soil fertility of our republic is decreasing, indicators that reduce soil fertility and quality are being studied, and measures are being taken to improve them. These foreign countries such as New Zealand, America, Colombia, Sweden and several other countries have emphasized the importance of soil health in ensuring high yields, the role of soil health assessment and its use in ensuring agriculture and food security. In our republic, data on the development of recommendations and practical measures on soil health and its indicators was analyzed.